Identification of Land Cover Changes in The MK-PHR Conservation Area Associated With Fire Events - Raden Putra; Tastaptyani Kurnia Nufutomo; Yuni Lisafitri; Novi Kartika Sari; Alfian Zurfi; Yanies Meiyanti (Indonesian Journal of Environmental Management and Sustainability, 2021)
Peat fire is one of the most environmental issues in Indonesia, particularly in the region of South Sumatra. The fires usually occur during the dry season from Juni to November. This study is designed to evaluate the impact of peat fires on changes in land cover in the Merang Kepahyang Peat Hydrological Region (MK-PHR) for the period of 2002 to 2015. The changes identified by the Normalized Difference Vegetation Index (NDVI) method using Landsat satellite imagery. The results of the study show that extreme peat fire associated with climate anomalies events occurred in 2006, 2012, and 2015. The largest peat fires during the observation period occurred in 2015 coincided with extreme climate anomalies generating negative changes in land cover in the most of MK-PHR areas. The changes occurred in almost half (49%) of the MK-PHR area, where it moved from the dense to moderate vegetation class. The spatial and temporal land cover changes will be discussed in more detail.